SOCIALIZATION ON PREVENTING THE SPREAD OF HOAX NEWS IN ONLINE NEWS MEDIA AT GROGOL VILLAGE, WERU, SUKOHARJO - Wijayanto, Danar Susilo; Kusumawati, Wahyu (Abdi Masya, 2025)
The socialization activity on hoax news in Grogol Village, Weru Subdistrict, Sukoharjo Regency, was conducted to increase public awareness about the dangers of hoax news and ways to prevent it. Using a community education approach, the team provided education on the definition, characteristics, and risks of hoax news, as well as how to protect themselves from the spread of fake news. This activity involved hands-on practice of checking the truth of the news using the website cekhoaks.id and promoting the habit of "Filter before sharing". A total of 50 residents actively participated in the "Facts Against Hoax: Socialization of Protecting Yourself from the Spread of Hoax News". As a result, the people of Grogol Village showed an increased awareness to check the content of news before sharing it. This activity is expected to minimize the spread of hoax news in the community and become part of a more critical culture in using social media. Thus, the people of Grogol Village can be wiser in dealing with information circulating on social media, so as to maintain the security and integrity of information in their community.